2020
DOI: 10.2147/ott.s268593
|View full text |Cite
|
Sign up to set email alerts
|

<p>Durable Response to Osimertinib in a Chinese Patient with Metastatic Lung Adenocarcinoma Harboring a Rare EGFR L858R/D761Y Compound Mutation</p>

Abstract: Uncommon mutations account for 10-15% of epidermal growth factor receptor (EGFR) mutations in patients with non-small-cell lung cancer (NSCLC). However, in spite of the wealth of knowledge of the clinical significance and tyrosine kinase inhibitor (TKI) sensitivity of these mutations, acquisition of deeper insights is limited by the paucity of case reports and cohort studies of the exceptionally rare mutations, including compound mutations. In the present case, we describe the clinical efficacy of icotinib and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…A 62-year-old non-smoking woman with advanced lung adenocarcinoma who responded with stable disease (SD) to sequential treatments with Icotinib and Osimertinib, the PFS with Osimertinib treatment is much longer than that with Icotinib (19 months vs 8.2 months) and the OS is more than 3 years. [13] Besides, an in vitro study has showed that despite displaying resistance to first-generation reversible EGFR-TKIs, L858R/D761Y mutant cells were sensitive to irreversible inhibitors, especially the third-generation EGFR-TKIs. [14] However, in this case, we reported a lung adenocarcinoma patient carrying D761Y mutation present before EGFR-TKI treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A 62-year-old non-smoking woman with advanced lung adenocarcinoma who responded with stable disease (SD) to sequential treatments with Icotinib and Osimertinib, the PFS with Osimertinib treatment is much longer than that with Icotinib (19 months vs 8.2 months) and the OS is more than 3 years. [13] Besides, an in vitro study has showed that despite displaying resistance to first-generation reversible EGFR-TKIs, L858R/D761Y mutant cells were sensitive to irreversible inhibitors, especially the third-generation EGFR-TKIs. [14] However, in this case, we reported a lung adenocarcinoma patient carrying D761Y mutation present before EGFR-TKI treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Another case reported a patient carrying an uncommon L858R/D761Y compound mutation in EGFR. Osimertinib treatment lead to a PFS of 19 months and OS of more than 3 years ( 24 ).…”
Section: The Efficacy Of Osimertinib In Nsclc Patients With Uncommon ...mentioning
confidence: 99%